Around the texts of writing center work : an inquiry-based approach to tutor education - Hall, R. Mark (Utah State University Press, 2017)
"Hall reveals the conceptual frameworks found in and created by ordinary writing center documents. The values and beliefs underlying course syllabi, policy statements, website copy and comments, assessment plans, promotional flyers, and annual reports all critically inform writing center practices, including the vital undertaking of tutor education."--Provided by publisher.